Stimulasi Auditori Menggunakan Murottal terhadap Vital Signs Pasien Stroke Fase Akut - Irman Irman; Dhea Natashia; Dewi Gayatri (Jurnal Keperawatan Silampari, 2021)
This study aims to determine the effect of auditory stimulus therapy using murotal on changes in vital signs in acute phase stroke patients. This research is a Randomized Controlled Trial (RCT) with the single-blind method and parallel design without matching. The results of statistical tests using the T-test to determine the difference in the mean decrease in the five vital signs showed that there was a decrease in the average pain scale, blood pressure, and heart rate in the intervention group, which was more significant than the control group (p-value < 0,05). In conclusion, auditory stimulation therapy using murotal significantly reduces pain scale, blood pressure, and heart rate in acute phase stroke patients. Keywords: Murotal, Auditory Stimulation, Acute Phase Stroke, TTV